Factors affecting the outbound open innovation strategies in pharmaceutical industry: Focus on out-licensing deal - Insoo Lee; Eungdo Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
The pharmaceutical industry is a high-technology industry that requires a combination of in-depth knowledge from various fields. It is characterized by high cost, high risk and a long-term perspective due to the high level of regulation. In addition, it is known that research and development (R&D) productivity is deteriorating in the industry. Under these conditions, the importance of open innovation strategies has been emphasized. Under an open innovation system, it is essential for firms to develop several dynamic capabilities to effectively manage their resources both internally and externally. Using a systematic framework of dynamic capabilities suggested by previous studies, this study focuses on the determinants affecting firms' desorptive capacities, which are measured as the number of out-licensing deals, as an indicator for the performance of their outbound innovation. For the analysis, negative binomial regression is employed and inventive capacity and connective capacity are selected as the determinants of the licensors' desorptive capacity. The results of regression analysis reveal that inventive capacity does not have a significant effect on desorptive capacity and that only connective capacity has a significant positive effect on desorptive capacity.
Keywords: 650; connective capacity; desorptive capacity; out-licensing; outbound open innovation; pharmaceutical industry